The von Willebrand Factor Facilitates Model for End‐Stage Liver Disease–Independent Risk Stratification on the Waiting List for Liver Transplantation. Issue 2 (23rd April 2020) - Györi, Georg P.; Pereyra, David; Rumpf, Benedikt; Hackl, Hubert; Köditz, Christoph; Ortmayr, Gregor; Reiberger, Thomas; Trauner, Michael; Berlakovich, Gabriela A.; Starlinger, Patrick
Abstract : Background and Aims: The Model for End‐Stage Liver Disease (MELD) is used for clinical decision‐making and organ allocation for orthotopic liver transplantation (OLT) and was previously upgraded through inclusion of serum sodium (Na) concentrations (MELD‐Na). However, MELD‐Na may underestimate complications arising from portal hypertension or infection. The von Willebrand factor (vWF) antigen (vWF‐Ag) correlates with portal pressure and seems capable of predicting complications in patients with cirrhosis. Accordingly, this study aimed to evaluate vWF‐Ag as an adjunct surrogate marker for risk stratification on the waiting list for OLT. Approach and Results: Hence, WF‐Ag at time of listing was assessed in patients listed for OLT. Clinical characteristics, MELD‐Na, and mortality on the waiting list were recorded. Prediction of 3‐month waiting‐list survival was assessed by receiver operating characteristics and net reclassification improvement. Interestingly, patients dying within 3 months on the waiting list displayed elevated levels of vWF‐Ag ( P  < 0.001). MELD‐Na and vWF‐Ag were comparable and independent in their predictive potential for 3‐month mortality on the waiting list (area under the curve [AUC], vWF‐Ag = 0.739; MELD‐Na = 0.764). Importantly, a vWF‐Ag cutoff at 413% identified patients at risk for death within 3 months of listing with a higher odds ratio (OR) than the previously published cutoff at a MELD‐Na of 20 points (vWF‐Ag, OR = 10.873, 95% confidence interval [CI], 3.160, 36.084; MELD‐Na, OR = 7.594, 95% CI, 2.578, 22.372; P  < 0.001, respectively). Ultimately, inclusion of vWF‐Ag into the MELD‐Na equation significantly improved prediction of 3‐month waiting‐list mortality (AUC, MELD‐Na–vWF = 0.804). Conclusions: A single measurement of vWF‐Ag at listing for OLT predicts early mortality. Combining vWF‐Ag levels with MELD‐Na improves risk stratification and may help to prioritize organ allocation to decrease waiting‐list mortality.